Retrospective study on the impact of ulnar nerve dislocation on the pathophysiology of ulnar neuropathy at the elbow - Seok Kang (PeerJ, 2019)
Introduction High resolution ultrasonography (US) has been used for diagnosis and evaluation of entrapment peripheral neuropathy. Ulnar neuropathy at the elbow (UNE) is the second most common focal entrapment neuropathy. The ulnar nerve tends to move to the anteromedial side and sometimes subluxates or dislocates over the medial epicondyle as the elbow is flexed. Dislocation of the ulnar nerve during elbow flexion may contribute to friction injury. We aimed to investigate the effects which the dislocation of ulnar nerve at the elbow could have on the electrophysiologic pathology of UNE. Materials We retrospectively reviewed 71 arms of UNE. The demographic data, electrodiagnosis findings and US findings of ulnar nerve were analyzed. We classified the electrodiagnosis findings of UNE into three pathologic types; demyelinating, sensory axonal loss, and mixed sensorimotor axonal loss. The arms were grouped into non-dislocation, partial dislocation, and complete dislocation groups according to the findings of nerve dislocation in US examination. We compared the electrodiagnosis findings, ulnar nerve cross sectional areas in US and electrodiagnosis pathology types among the groups. Results A total of 18 (25.3%) arms showed partial dislocation, and 15 (21.1%) arms showed complete dislocation of ulnar nerve in US. In the comparison of electrodiagnosis findings, the partial and complete dislocation groups showed significantly slower conduction velocities and lower amplitudes than non-dislocation group in motor conduction study. In the sensory conduction study, the conduction velocity was significantly slower in partial dislocation group and the amplitude was significantly lower in complete dislocation group than non-dislocation group. In the comparison of US findings, patients in partial and complete dislocation groups showed significantly larger cross sectional areas of the ulnar nerve. The comparison of electrodiagnosis pathologic types among the groups revealed that there were significantly larger proportions of the axonal loss (sensory axonal loss or mixed sensorimotor axonal loss) in partial and complete dislocation groups than non-dislocation group. Conclusion The ulnar nerve dislocation could influence on the more severe damage of the ulnar nerve in patients with UNE. It might be important to evaluate the dislocation of the ulnar nerve using US in diagnosing ulnar neuropathy for predicting the prognosis and determining the treatment direction of UNE.